A work study on Mama Rosa Foods owned and operated by Cater King Food Corporation - Cayanong, Kirby Luke Manalo (College of Engineering, 2000)
Methods Engineering is concerned mainly with measuring productivity and efficiency, and improving these in order to better the performance and gain of a company. Generally, through the knowledge and proper practice of the subject, any type of business could be improved by methods engineering. The researchers chose Mama Rose Corporation, which can be classified as a budding player in the food industry, to conduct a work study on. The company's type of status, according to critics, is prone to the so called beginner's error. Having been established in 1976 as a single proprietorship, which specializes in selected lines of regional delicacies, Mama Rosa is in need of much improvement and standardization in its highly manual operations. Its top selling bagoong (shrimp paste) seemed to be in need of most attention, as its full production potential is hindered by factors which can be dealt with using the tools of methods engineering. Also, it would be most beneficial for the company to focus on this particular problem area in its operations since bagoong is one of its most, if not the most, profitable product. As the researcherse conducted the necessary plant visits, they tried to be wary of every possible detail, and to identify as many problems as possible. There were actually nine problems identified by the researchers, but since the major concern was to improve the productivity of the company, root causes were focused on with the help of the knowledge in problem analysis. The researchers were able to narrow down the root problems in three. These are : (1) the primary raw material is scarce; (2) the kitchen area is generic to all products; and (3) the use of burners is not well delegated. Alternative solutions were formulated, and by means of the techniques learned in IE 32, like the use of streamline analysis and the Ishikawa diagram time study, evaluation of must and want objectives, layout design and others, solutions were reached. These are : (1) to advertise the need for more sources of shrimp fry; (2) to change the existing kitchen layout; (3) to create a schedule for the use of burners, respectively. It is the hope of the researchers that these solutions will be of help to the company under study.